The Concept of Religious Tolerance of Muhammadiyah and Nahdlatul Ulama in the Harmony of Religious Communities in Indonesia - Afna Fitria Sari; Tobroni Tobroni; Fritz Hotman Syahmahita Damanik (Universitas Darussalam Gontor, 2026)
This study aims to analyze and compare the concepts of religious tolerance according to Muhammadiyah and Nahdlatul Ulama (NU), and to explain their contributions to strengthening interfaith harmony in Indonesia. This study uses a qualitative approach with library research to examine the similarities and differences in the concepts of tolerance between Muhammadiyah and NU. The results show that Muhammadiyah emphasizes the concept of Progressive Islam which is rational, modern, and oriented towards universal humanitarian values, while Nahdlatul Ulama developed the concept of Islam Nusantara which emphasizes local wisdom, cultural traditions, and social harmony. Although different in theological and cultural approaches, both share similarities in upholding the principles of rahmatan lil 'alamin and religious moderation. The combination of Muhammadiyah's rational values ​​and NU's cultural wisdom has become a strong foundation in building interfaith harmony in Indonesia. This study confirms that the synergy between Muhammadiyah and NU is a strategic factor in strengthening tolerance and national unity. Keywords: Religious tolerance, Muhammadiyah, Nahdlatul Ulama